Metabolomics of the interaction between PPAR-? and age in the PPAR-?-null mouse - Atherton, Helen J. (2009)
Regulation between the fed and fasted states in mammals is partially controlled by peroxisome proliferator-activated receptor-alpha (PPAR-alpha). Expression of the receptor is high in tissues with a high catabolic rate such as the liver, heart and skeletal muscle, and its activation results in the downstream transcription of genes controlling fatty acid transport, uptake, intracellular binding and catabolism. The role of PPAR-alpha in the transition between the fed and fasted states has been extensively characterised, but its role in ageing has been much less studied. It is known, however, that the expression of this receptor decreases with age in a number of tissues including the liver and heart. In this study, a combined 1H-NMR spectroscopy and GC-MS-based metabolomic approach has been used to examine the interactions between systemic metabolism, loss of PPAR-alpha and the age of the animal, in the liver, heart, skeletal muscle and white adipose tissue in PPAR-alpha-null mice and wild-type controls aged between 3 and 13 months. Data were analysed using multivariate statistics.